Circadian clocks: lessons from fish - Idda, Maria Laura; Foulkes, Nicholas S. (The neurobiology of circadian timing, 2012)
Our understanding of the molecular and cellular organization of the circadian timing system in vertebrates has increased enormously over the past decade. In large part, progress has been based on genetic studies in the mouse as well as on fundamental similarities between vertebrate and Drosophila clocks. The zebrafish was initially considered as a potentially attractive genetic model for identifying vertebrate clock genes. However, instead, fish have ultimately proven to be valuable complementary models for studying various aspects of clock biology. For example, many fish can shift from diurnal to nocturnal activity implying specific flexibility in their clock function. We have learned much about the function of light input pathways, and the ontogeny and function of the pineal organ, the fish central pacemaker. Finally, blind cavefish have also provided new insight into the evolution of the circadian clock under extreme environmental conditions.